2008
DOI: 10.1021/cg070125g
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transport Phenomena during Bridgman Growth of Calcium Fluoride Doped Crystals

Abstract: The chemical homogeneity of CaF 2 :Pb crystals, grown by using the vertical Bridgman method, is numerically investigated. The FIDAP commercial code is used to study the heat transfer, convection, and solute transport phenomena during the solidification process. The homogeneity of these doped crystals depends on the solid-liquid interface curvature and the flow intensity. The accurate computation of the thermal field and interface shape for these semitransparent materials requires the modeling of the internal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Extensive experimental [1][2][3] and numerical studies [4][5][6] have shown that the solute distribution in crystals depends on the physical properties of the given alloy, the growth rate and the flow intensity. Unexpected oscillations in the longitudinal solutal profile have been detected in some Bridgman solidification experiments of doped semiconductors [7,8] and fluoride crystals [9]. The particularity of these experiments consists in a low level of the melt convection as shown by previous numerical simulations [10,11].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Extensive experimental [1][2][3] and numerical studies [4][5][6] have shown that the solute distribution in crystals depends on the physical properties of the given alloy, the growth rate and the flow intensity. Unexpected oscillations in the longitudinal solutal profile have been detected in some Bridgman solidification experiments of doped semiconductors [7,8] and fluoride crystals [9]. The particularity of these experiments consists in a low level of the melt convection as shown by previous numerical simulations [10,11].…”
Section: Introductionmentioning
confidence: 88%
“…More details about the modeling of doped semiconductor and calcium fluoride crystals are given in Refs. [10,11].…”
Section: Numerical Simulationmentioning
confidence: 99%
See 3 more Smart Citations